(untitled) (CAHIERS MAGELLANES-NS, 2024)
Introduction: Basti, one of the Panchakarma therapies in Ayurveda, is a vital treatment for cleansing and balancing the body’s doshas. It is particularly effective in treating Vata-related disorders but is also used to address a wide range of health conditions, from digestive issues to chronic illnesses. Practitioner’s prime obligation is to consider the patient’s fitness prior to any Panchakarma treatment. In classics clearly Yogya (Fit) and Ayogya (Unfit) criteria are mentioned for basti, which are assessed before planning basti treatment. The present data collected on Basti will clearly indicate the need for an approach to the patient using a basti fitness assessment form in clinical practice. Objective: To develop the Basti fitness form for use in clinical settings with the intention of minimizing atypical issues and optimizing the intended outcome. Materials and Methods: To create the fitness form, literature on Basti karma, guda śarīra with rectum anatomy, rectum examination, and other anatomical disorders were taken into consideration. This form was applied to 200 patients undergoing basti treatment at KAHER’s Shri B.M.Kankanwadi Ayurveda Mahavidhyalaya. PG Studies and Research Center and over 50 patients at SBG Ayurveda College Belagavi, which helped for quick screening for commonly occurring Ano-rectal problems which hinder practice of basti, precautionary practices were followed to minimize the possible complications. Results: Out of 250 patients screened for basti pre assessment fitness 213 (85.2%) patients were fit for basti, inculcating this pre assessment basti fitness practice engendered to receive basti treatment by 244 (97.6%) patients without any discomfort and complications. Conclusion: The current fitness structure will assist in achieving the best possible outcomes and preventing atypical consequences in addition to assisting in the assessment of anal diseases, which pose challenges to drug delivery.